Catalytic processes for API synthesis : from laboratory to industry /: from laboratory to industry. (2018) - Burke, Anthony J (Anthony Joseph); Marques, Carolina Silva, 1981-; Turner, N. J (Nicholas J.); Hermann, Gesine J
No abstract available